Serotonin System Implication in l-DOPA-Induced Dyskinesia: From Animal Models to Clinical Investigations - Carta, Manolo; Tronci, Elisabetta (Frontiers in Neurology, 2014)
In the recent years, the serotonin system has emerged as a key player in the induction of l-DOPA-induced dyskinesia (LID) in animal models of Parkinson’s disease. In fact, serotonin neurons possess the enzymatic machinery able to convert exogenous l-DOPA to dopamine (DA), and mediate its vesicular storage and release. However, serotonin neurons lack a feedback control mechanism able to regulate synaptic DA levels. While in a situation of partial DA depletion spared DA terminals can buffer DA released from serotonin neurons, the progression of DA neuron degeneration impairs this protective mechanism, causing swings in synaptic DA levels and pulsatile stimulation of post-synaptic DA receptors. In line with this view, removal of serotonin neurons by selective toxin, or pharmacological silencing of their activity, produced complete suppression of LID in animal models of Parkinson’s disease. In this article, we will revise the experimental evidence pointing to the important role of serotonin neurons in dyskinesia, and we will discuss the clinical implications.